Improvement of urinary dysfunction after kidney transplantation by administration of the antimuscarinic agent--prospective randomized controlled study - Tsunoyama, Kuniko; Ishida, Hideki; Shimizu, Tomokazu; Omoto, Kazuya; Tanabe, Kazunari (Transplantation, 2012)
Bladder dysfunction after kidney transplantation (KTx) impairs the patients' quality of life. We examined the bladder function status perioperatively in patients undergoing KTx and performed a randomized prospective study to determine the efficacy of an antimuscarinic agent, solifenacin, in ameliorating the bladder dysfunction after KTx. The subjects in this study were 33 patients who underwent KTx at our institution. The patients were divided into two groups: group 1 (n=18), composed of patients who were not treated with any antimuscarinic agent, and group 2 (n=15), composed of patients treated with an antimuscarinic agent. We investigated the actual bladder function status of these patients before and after KTx by the following two methods: (1) video water cystometry and (2) questionnaire study using the Overactive Bladder Symptom Score and King's Health Questionnaire. The cystometry study revealed a significantly greater increase of the maximum cystometric capacity in group 2 than in group 1 (173.0±60.7 mL in group 1 and 260.1±51.0 mL in group 2 [P=0.005]) after KTx. In the questionnaire surveys, the decreases in the scores for all domains were observed 6 weeks after KTx. The scores in group 2 tended to be lower than those in group 1. In all of our patients, the bladder dysfunction status improved dramatically after KTx. In addition, our results suggest that administration of the antimuscarinic agent, solifenacin, may contribute to improvement of the quality of life of patients undergoing KTx.